2014
DOI: 10.1038/npp.2014.175
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal GLP-1 Receptors Influence Food Intake, Meal Size, and Effort-Based Responding for Food through Volume Transmission

Abstract: Glucagon-like peptide-1 (GLP-1) is produced in the small intestines and in nucleus tractus solitarius (NTS) neurons. Activation of central GLP-1 receptors (GLP-1Rs) reduces feeding and body weight. The neural circuits mediating these effects are only partially understood. Here we investigate the inhibition of food intake and motivated responding for food in rats following GLP-1R activation in the ventral hippocampal formation (HPFv), a region only recently highlighted in food intake control. Increased HPFv GLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(154 citation statements)
references
References 57 publications
(82 reference statements)
8
145
1
Order By: Relevance
“…For instance, while the ventral hippocampus has bi-directional connections to the amygdala, the dorsal hippocampus does not have any [33]. Moreover, as mentioned before, GLP-I receptors in the ventral hippocampus, but not in the dorsal hippocampus, influence food intake and willingness to work to obtain food [65,81]. However, the respective roles of the ventral and dorsal hippocampus in meal onset are not currently known [117].…”
Section: Interactions Between the Amygdala And The Hippocampusmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, while the ventral hippocampus has bi-directional connections to the amygdala, the dorsal hippocampus does not have any [33]. Moreover, as mentioned before, GLP-I receptors in the ventral hippocampus, but not in the dorsal hippocampus, influence food intake and willingness to work to obtain food [65,81]. However, the respective roles of the ventral and dorsal hippocampus in meal onset are not currently known [117].…”
Section: Interactions Between the Amygdala And The Hippocampusmentioning
confidence: 94%
“…For instance, Hsu et al [66] have shown that ghrelin signaling in the hippocampus can stimulate conditioned appetite. Additionally, glucagon-like peptide-I (GLP-I) receptors in the ventral hippocampus also influence food intake and willingness to work to obtain food (i.e., "wanting"; [65,81]). Furthermore, there is solid evidence showing that hippocampal neurons form a memory of a meal and inhibit meal onset after a meal has been consumed [53,115,117].…”
Section: Hippocampus and The Use Of Interoceptive Signals Of Hunger Amentioning
confidence: 99%
“…naling across the blood-cerebrospinal fluid-brain and bloodbrain barrier (22); however, for hormones such as leptin, the importance of volume transmission still needs to be established. Our current data provide no evidence either for or against this mechanism, and additional experiments are needed in order include or exclude the probability of this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with this conversion in the dorsal hippocampus increases weight gain in rodents [29]. In the ventral hippocampus, activation of receptors for the anorectic peptides leptin and GLP-1 decreases food intake and appetitive behavior based on food rewards [30, 31], whereas direct administration of the orexigenic hormone ghrelin (which presumably antagonizes satiety signaling) increases meal frequency and the ability of environmental food-related cues to stimulate eating [32]. These results suggest that interference with the hippocampal processing of either anorectic or orexigenic promotes positive energy balance.…”
Section: Supporting Datamentioning
confidence: 99%